A prospective randomised controlled study on the effects of myoinositol on ovarian functions and metabolic factors in women with polycystic ovarian syndrome - Singh, Pooja; Biswal, Suchismita; Verma, Santosh Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Polycystic ovary syndrome is one of the most common endocrine disorder affecting five to ten percent women of reproductive age group. Myoinositol has been reported to be helpful in PCOS women with deranged metabolic and ovarian factors. In this study, we have evaluated the effects of myoinositol in women with PCOS. Methods: A total of 132 patients are included in the study. 66 patients in the study group were given myoinositol 4 gm daily for three months, while other 66 patients in the control group were given folic acid for the same duration. The parameters were evaluated at the beginning, six and twelve weeks after intervention. Results: After completion of 12 weeks, myoinositol was found to have a significant effect on reduction of BMI of the patients. No changes was seen in the fasting insulin levels, but a significant decrease in fasting blood sugar levels of patients was seen. Also, a significant increase in serum HDL was seen in the study group. Luteal phase serum progesterone was also increased in the study group. Conclusions: Myoinositol has got noticeable effects in reducing the BMI of PCOS women. We didn’t find any significant effect of the drug over the fasting insulin level. Serum HDL was increased in some patients. An increase in luteal phase progesterone was noticed which suggest that myoinositol may be beneficial in ovulation. However further studies are needed to establish the same.